Flocculation behavior of colloidal suspension by use of inorganic and polymer flocculants in powder form. (August 2017) - Kadooka, Hiroto; Kiso, Yukari; Goto, Shotaro; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi
Highlights: Full investigation of the composite dry powdered flocculant is conducted. The suitable dosage of the polymer depends on the dosage of inorganic salt. Combinations of inorganic and polymer flocculant affect floc property. A procedure for determining an optimum composition is proposed. Abstract: The clarification method by using composite dry powdered flocculants consisting of inorganic flocculant, polymer flocculant and flocculation aid has been proposed in the literature. Such composite flocculants are conveniently used in the flocculation process of small volume suspensions; i.e. the composite dry powdered flocculants are added directly to a suspension. However, very limited work has been reported on the flocculation behavior when composite flocculants are used in powder form. In this study, the effect of both dosages of dry powdered inorganic flocculant and ionic polymer flocculant on turbidity removal of PMMA suspension is investigated. Floc characteristics, such as sludge volume and floc strength, are also discussed. It is found that there exist various combinations of inorganic and polymer flocculant dosages resulting in sufficient turbidity removal; as the dosage of inorganic flocculant is increased, the suitable dosage of ionic polymer flocculant is also increased for better turbidity removal. Among these combinations of inorganic and polymer flocculant dosages, floc strength in higher dosages is larger than that in lower dosages. It is also found that in the higher polymer dosage conditions, flocculated sludge shows both local minimum and local maximum volume depending on dosage of inorganic flocculant. From these results, variations of polymer flocculant morphology under various inorganic flocculant dosages are discussed. A procedure for determining the optimum composition of a composite dry powdered flocculant for turbidity removal is proposed.